High-risk prostate cancer treated with a stereotactic body radiation therapy boost following pelvic nodal irradiation - Lischalk, Jonathan W.; Akerman, Meredith; Repka, Michael C.; Sanchez, Astrid; Mendez, Christopher; Santos, Vianca F.; Carpenter, Todd; Wise, David; Corcoran, Anthony; Lepor, Herbert; Katz, Aaron; Haas, Jonathan A. (Frontiers in Oncology, 2024)
Modern literature has demonstrated improvements in long-term biochemical outcomes with the use of prophylactic pelvic nodal irradiation followed by a brachytherapy boost in the management of high-risk prostate cancer.However, this comes at the cost of increased treatment-related toxicity. In this study, we explore the outcomes of the largest cohort to date, which uses a stereotactic body radiation therapy (SBRT) boost following pelvic nodal radiation for exclusively high-risk prostate cancerA large institutional database was interrogated to identify all patients with high-risk clinically node negative prostate cancer treated with conventionally fractionated radiotherapy to the pelvis followed by a robotic SBRT boost to the prostate and seminal vesicles. The boost was uniformly delivered over three fractions. Toxicity was measured using Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. Oncologic outcomes were assessed using the Kaplan Meier method. Cox proportional hazard models were created to evaluate associations between pretreatment characteristics and clinical outcomes.A total of 440 patients with a median age of 71 years were treated, the majority of which were diagnosed with grade group 4 or 5 disease. Pelvic nodal irradiation was delivered to a total dose of 4500 cGy in 25 fractions followed by a 3 fraction SBRT boost. With early median follow up of 2.5 years, the crude incidence of grade 2+ Genitourinary (GU) and Gastrointestinal (GI) toxicity was 13% and 11%, respectively. Multivariate analysis revealed grade 2+ GU toxicity was associated with older age and higher American Joint Committee on Cancer (AJCC) stage.Multivariate analysis revealed overall survival was associated with patient age and post-treatment Prostate-Specific Antigen (PSA) nadir.Utilization of an SBRT boost following pelvic nodal irradiation in the treatment of high-risk prostate cancer is oncologically effective with early follow up and yields minimal high-grade toxicity. We demonstrate a 5-year freedom from biochemical recurrence (FFBCR) of over 83% with correspondingly limited grade 3+ GU and GI toxicity measured at 3.6% and 1.6%, respectively. Long-term follow up is required to evaluate oncologic outcomes and late toxicity.